Nutrient Consumption and Household Income in Rural Mexico - Skoufias, Emmanuel; Di Maro, Vincenzo; Gonzalez-Cossio, Teresa; Rodriguez Ramirez, Sonia (2012)
We estimate the income elasticity for a variety of macro- and micronutrients using a sample of poor rural households in Mexico. The nutrient-income elasticity is estimated using both parametric and semiparametric methods. A special focus is placed on the nonlinearity of the relationship between nutrient intake and income and on measurement error and endogeneity issues. One major finding is that income elasticity for calories is close to zero when we control for measurement error issues. For some nutrients, namely fats, vitamin A and C, calcium, and heme iron, we find a sizeable positive income elasticity robust to the choice of the estimator and percentiles at which it is evaluated. These nutrients are also those for which we find the largest deficiency in our sample. In addition, we find that for the poorest households in our sample, the deficiency of total energy, protein, and zinc is not accompanied by a positive income elasticity.